Pengawasan Pelaksanaan Otonomi Daerah - Mhd Ansori (Universitas Batanghari Jambi, 2018)
Supervision is a part of the overall authority of the government, because at the last level the Central Government must be responsible for the whole administration, justifying the holding of supervision of all regional actions, because the integrity of the Unitary State must be maintained. Regional autonomy as autonomy for regional people and not